Type 1 Diabetes Prevention: Screening Efforts and Prevention Studies in At-Risk Relatives and the General Population - Farkas, Hal Steven; Leschek, Ellen Werber (Medical Research Archives, 2025)
Type 1 diabetes autoantibodies are detectable before the onset of clinical disease. Once an individual has ≥2 diabetes autoantibodies, their lifetime risk of developing clinical disease approaches 100%. While relatives of individuals with type 1 diabetes have a 15-fold increase in disease risk, 85-95% of type 1 diabetes diagnoses occur in people without affected relatives. Identification of multiple diabetes autoantibodies and subsequent education and monitoring prior to clinical type 1 diabetes diagnosis decreases the incidence of diabetic ketoacidosis at onset as well as other diabetes sequelae. Also, early risk recognition facilitates participation in clinical trials aimed at delay and prevention of clinical disease and/or treatment with teplizumab, an approved medication to delay onset of clinical type 1 diabetes in people with multiple diabetes autoantibodies and dysglycemia. Therefore, risk screening, which is currently recommended only for relatives of individuals with type 1 diabetes, should be expanded to include the general population.